2019
DOI: 10.1097/pq9.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Goal Setting in Developmental Therapy: Discordance between Documented Goals and Caregiver-Perceived Goals

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Yet, while most occupational therapists perceived that their goal setting was family-centred, some child and parent participants felt it took a more therapist-directed approach. This is consistent with the findings of Angeli et al [ 54 ]. Parents confirmed that therapist decision-making takes priority, while therapists reported mainly giving priority to parent’s voice and working to balance expectations of parents.…”
Section: Discussionsupporting
confidence: 94%
“…Yet, while most occupational therapists perceived that their goal setting was family-centred, some child and parent participants felt it took a more therapist-directed approach. This is consistent with the findings of Angeli et al [ 54 ]. Parents confirmed that therapist decision-making takes priority, while therapists reported mainly giving priority to parent’s voice and working to balance expectations of parents.…”
Section: Discussionsupporting
confidence: 94%
“…A good quality relationship between patients, families and professionals is essential for achieving this goal (Angeli et al, 2019) There is a lack of studies that analyse the perceptions and experiences of parents of patients treated in ECI regarding their relationship with the professionals involved. Knowledge of these perceptions could help improve the implementation of PFCC in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there is a great interest in studying strategies to implement patient-centered care (PCC) in all areas of healthcare [1][2][3][4][5][6][7]. According to Morgan and Yoder [8], PCC is a "holistic (biopsycho-social-spiritual) approach to delivering care that is respectful and individualized, allowing negotiation of care, and offering choice through a therapeutic relationship where persons are empowered to participate in health decisions at whatever level is desired".…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant factors for the establishment of PCC is the quality of the therapeutic relationship, or the relationship that is established between the care providers and their patients [6][7][8][9][10][11][12][13]. There is growing consensus that the quality of care depends directly on communication and the relationship between patient and therapist, both in the field of physical therapy [4,5,[14][15][16][17][18][19] and in others [20].…”
Section: Introductionmentioning
confidence: 99%